2020
DOI: 10.1111/bju.15127
|View full text |Cite
|
Sign up to set email alerts
|

Favourable multi‐institutional experience with penoscrotal decompression for prolonged ischaemic priapism

Abstract: To report our multi-institutional experience using penoscrotal decompression (PSD) for the surgical treatment of prolonged ischaemic priapism (PIP). Materials and Methods We retrospectively reviewed clinical records for patients with PIP treated with PSD between 2017 and 2020. Priapisms were confirmed as ischaemic based on clinical presentations and cavernosal blood gas abnormalities. Treatment with irrigation and injection of a-agonists in all patients had failed prior to PSD. Patient characteristics, peri-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Subsequently, nine (60%) reported spontaneous erectile function adequate for penetration, and six (40%) reported erectile dysfunction. The study established that PSD is a simple, safe, and highly effective treatment for refractory ischaemic priapism; however, further larger prospective studies and randomised controlled trials are required to confirm these findings 23 .…”
Section: Management Of Priapismmentioning
confidence: 85%
See 1 more Smart Citation
“…Subsequently, nine (60%) reported spontaneous erectile function adequate for penetration, and six (40%) reported erectile dysfunction. The study established that PSD is a simple, safe, and highly effective treatment for refractory ischaemic priapism; however, further larger prospective studies and randomised controlled trials are required to confirm these findings 23 .…”
Section: Management Of Priapismmentioning
confidence: 85%
“…This glans-sparing corporal decompression technique aims to allow spontaneous recovery of erectile function and therefore reduce the need for implantation of a penile prosthesis 22 . A recent retrospective multicentre study reported on 10 patients undergoing unilateral PSD, of whom two (20%) had a recurrence of priapism 23 . A further 15 patients underwent primary bilateral PSD; none had priapism recurrence.…”
Section: Management Of Priapismmentioning
confidence: 99%
“…We favor PSD over distal shunts based on our experience and early multi-institutional data showing its safety, efficacy, and promising outcomes. 5 Interestingly, the patient had tolerated the same dose for 6 years in a row without experiencing priapism or any other adverse effect.…”
Section: Discussionmentioning
confidence: 96%
“…Recent data on penoscrotal decompression (PSD) has shown promising outcomes as a viable salvage or alternative strategy for management of refractory ischemic priapism and has become our preferred technique. 5 We report a priapism case presenting with a unique etiology, with an unelucidated mechanism of action. Our aim is to promote education to both patients and clinicians regarding this rare side effect of melanotan II (MT II), as well as integrate MC analogs into the risk assessment of use of drugs that may precipitate priapism.…”
Section: Introductionmentioning
confidence: 98%
“…In this issue of the BJUI , Morey et al [5] describe their multi‐institutional experience of treating ischaemic priapism by Penoscrotal decompression (PSD). The advantages of the PSD technique is that it involves a larger decompression to allow a thorough washout of the cavernosa, and it avoids breaching the distal tunica and therefore reducing potential penile prostheses complications in the future if needed.…”
mentioning
confidence: 99%